The metamorphosis of metaphor: from literary trope to conceptual key - Angélica, Julia C. (Lenguas Modernas, 2017)
The study of metaphor has long been hampercd by the post-Aristotelian bias that metaphor is mere poetic figurative language. Such bias has been compounded by sequential models of cognitive processes cemented into scientific (and subsequently psychological) literature. During the last decade, however, cognitive scientists have begun to re-cvaluate thc importancc of metaphor as a key element in abstract thinking, realizing particularly thc universality of the metaphoric dynamic. This focus has been further underscored by findings in cognitive neuroscience that show both that languagc proccssing involves visual, motor, auditory, and other neural systems, and that multimodal experiences related to metaphor may converge in central processing areas. Further, they have noted that, rather than being geographically localized, language processing is distributed throughout the brain. To explain this distribution, one anthropological model proposes that growing societal complexity necessitated increased linguistic development for which the brain adapted existing brain areas. Such investigative insights support the assumption that metaphor -far from being a mere literary embellishment- is in reality a key element in the cognitive inferences by which all language users interpret and cope with their expcriential world.